Long noncoding RNAs: functions and mechanisms in colon cancer - Chen, Sian (Mol Cancer, 2020)
Evidence indicates that long non-coding RNAs (lncRNAs) play a crucial role in the carcinogenesis and progression of a wide variety of human malignancies including colon cancer. In this review, we describe the functions and mechanisms of lncRNAs involved in colon oncogenesis, such as HOTAIR, PVT1, H19, MALAT1, SNHG1, SNHG7, SNHG15, TUG1, XIST, ROR and ZEB1-AS1. We summarize the roles of lncRNAs in regulating cell proliferation, cell apoptotic death, the cell cycle, cell migrative and invasive ability, epithelial-mesenchymal transition (EMT), cancer stem cells and drug resistance in colon cancer. In addition, we briefly highlight the functions of circRNAs in colon tumorigenesis and progression, including circPPP1R12A, circPIP5K1A, circCTIC1, circ_0001313, circRNA_104916 and circRNA-ACAP2. This review provides the rationale for anticancer therapy via modulation of lncRNAs and circular RNAs (circRNAs) in colon carcinoma.